Hadapi Pandemi Covid-19 Dalam Pemberdayaan Pemerataan Di Perdesaan Dalam Manipol Usdek Sebagai Perspektif Pendidikan Politik Nawacita Jokowi Di Era Milenial - I Ketut Kasna (Jurnal Ilmiah Cakrawarti, 2021)
Inequality and poverty, especially in rural areas, are one of the challenges of the Indonesian nation. Compared to cities, the proportion of poor people due to the dilemma facing the Covid-19 pandemic is much higher in rural areas. Especially in remote villages, rural areas or underdeveloped areas, the conditions are much more apprehensive. Therefore, rural development is a priority. Large amounts of Village Funds are distributed and continue to increase every year for empowering the local economy, creating access to local transportation and fulfilling basic infrastructure as well as financing due to the dilemma facing the Covid-19 pandemic. To tackle poverty due to the Covid-19 pandemic in rural areas and overcome inequality between villages and villages and cities, the government has established a strategy of "building from the fringes of the dilemma facing the Covid-19 pandemic" according to the Nawacita agenda. The government believes that rural-based development is very important because it can strengthen the foundations of the country's economy and accelerate poverty eradication due to the dilemma facing the  Covid- 19 pandemic and reduce disparities between regions. The importance of the village is also recognized by non-government organizations. One of them is community exploration and services for welfare (Kompak), a partnership between the Indonesian and Australian governments. In a policy analysis report entitled: "VILLAGE FUNDING AND POVERTY TREATMENT DUE TO THE COVID-19 DILEMMA DUE TO PINDEMY": the expert team from the compact stated that the village had a strategic position as a basis for change.  Inequality and poverty, especially in rural areas, are one of the challenges of the Indonesian nation. Compared to cities, the proportion of poor people due to the dilemma facing the Covid-19 pandemic is much higher in rural areas. Especially in remote villages, rural areas or underdeveloped areas, the conditions are much more apprehensive. Therefore, rural development is a priority. Large amounts of Village Funds are distributed and continue to increase every year for empowering the local economy, creating access to local transportation and fulfilling basic infrastructure as well as financing due to the dilemma facing the Covid-19 pandemic. To tackle poverty due to the Covid-19 pandemic in rural areas and overcome inequality between villages and villages and cities, the government has established a strategy of "building from the fringes of the dilemma facing the Covid-19 pandemic" according to the Nawacita agenda. The government believes that rural-based development is very important because it can strengthen the foundations of the country's economy and accelerate poverty eradication due to the dilemma facing the  Covid- 19 pandemic and reduce disparities between regions. JURNAL CAKRAWARTI, VOL. 04 NO. 01 FEB-JUL 2021 I Ketut Kasna 67    The importance of the village is also recognized by non-government organizations. One of them is community exploration and services for welfare (Kompak), a partnership between the Indonesian and Australian governments. In a policy analysis report entitled: "VILLAGE FUNDING AND POVERTY TREATMENT DUE TO THE COVID-19 DILEMMA DUE TO PINDEMY": the expert team from the compact stated that the village had a strategic position as a basis for change.